A simulator based on virtual reality to dismantle a research reactor assembly using master-slave manipulators. (October 2018) - Nash, B.; Walker, A.; Chambers, T.
Highlights: Computer graphics can be used to provide insight into decommissioning operations. High-quality simulation is possible at low-cost. Simulation provides opportunities to develop improved processes. Skill development using low-cost hardware can enhance training. Games based learning provides opportunities for targeted development of skills. Abstract: The use of simulation within the nuclear industry has been limited by the perceived cost and benefits that such tools offer. In this paper, we present the development of a simulator based on the use of master-slave-manipulators to dismantle a small research reactor core assembly. We discuss the design of the simulator hardware and the different software elements that make up the system. We show how this type of tool can be used to explore various options during the development of a nuclear decommissioning process. Finally, we discuss the benefits that have been observed from using the system to support the decommissioning of the CONSORT research reactor.